Records Committee review for rare bird sighting of Lesser Black-backed Gull at Elk Rock State Park, 1986 - Fuller, James Let al (1986)
Records Committee review for a Lesser Black-backed Gull at Elk Rock State Park in Marion County, IA on December 11, 1986. Includes a record review document with votes, a summary of the review, and a documentation form submitted to the committee. Epson - sheet feed